Brønsted acid ionic liquid-catalyzed reductive Friedel–Crafts alkylation of indoles and cyclic ketones without using an external reductant. Issue 2 (26th November 2014) - Taheri, Amir; Lai, Bingbing; Cheng, Cheng; Gu, Yanlong
Abstract : C3-cycloalkylated indole was synthesized from indole and cyclic ketone in the absence of a reductant with the aid of an acid catalyst. Abstract : In the absence of an external reductant, C3-cycloalkylated indole could be synthesized through reductive alkylation of indole with cyclic ketone using a sulfonyl-functionalized Brønsted acid ionic liquid as a catalyst. Water generated in the initial stage of the reaction played a key role in rendering the reductive coupling possible. The reaction proceeds most likely in a radical way.